Correction: Crosslinking of comb-shaped polymer anion exchange membranes via thiol–ene click chemistry. Issue 14 (16th March 2016) - Zhu, Liang; Zimudzi, Tawanda J.; Li, Nanwen; Pan, Jing; Lin, Bencai; Hickner, Michael A.
Abstract : Correction for 'Crosslinking of comb-shaped polymer anion exchange membranes via thiol–ene click chemistry' by Liang Zhu, et al., Polym. Chem., 2016, DOI: 10.1039/c5py01911g.